2005
DOI: 10.1016/j.cell.2005.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Nicastrin Functions as a γ-Secretase-Substrate Receptor

Abstract: gamma-secretase catalyzes the intramembrane cleavage of amyloid precursor protein (APP) and Notch after their extracellular domains are shed by site-specific proteolysis. Nicastrin is an essential glycoprotein component of the gamma-secretase complex but has no known function. We now show that the ectodomain of nicastrin binds the new amino terminus that is generated upon proteolysis of the extracellular APP and Notch domains, thereby recruiting the APP and Notch substrates into the gamma-secretase complex. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
438
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 426 publications
(466 citation statements)
references
References 32 publications
23
438
2
3
Order By: Relevance
“…It has recently been shown that the extracellular domain of nicastrin is involved in the substrate recognition, whereas the transmembrane domain of the protein is critical in the assembly and trafficking of the γ-secretase complex to the cell surface [4,43]. The significance of this protein is further highlighted by RNAi and gene knock out studies, which clearly demonstrated that nicastrin is essential for the assembly of PS1/γ-secretase complex and secretion of Aβ peptide [20,30,31,54,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that the extracellular domain of nicastrin is involved in the substrate recognition, whereas the transmembrane domain of the protein is critical in the assembly and trafficking of the γ-secretase complex to the cell surface [4,43]. The significance of this protein is further highlighted by RNAi and gene knock out studies, which clearly demonstrated that nicastrin is essential for the assembly of PS1/γ-secretase complex and secretion of Aβ peptide [20,30,31,54,56].…”
Section: Discussionmentioning
confidence: 99%
“…Ectodomain shedding is a prerequisite for γ-secretase cleavage of substrates [47]. The extracellular domain of nicastrin binds to C-terminal stubs generated by ectodomain shedding of type I membrane protein substrates, thus recruiting substrates for cleavage by the γ-secretase [43].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to presenilin, which requires additional subunits for enzyme activity, the active SPP enzyme does not require additional subunits for activity (32). This implies that the additional subunits of ␥-secretase, which are essential for enzyme maturation, contribute only to non-catalytic functions, such as the recognition and binding of substrates by nicastrin (35,36). SPP therefore represents a simplified model for ␥-secretase.…”
mentioning
confidence: 99%
“…S2 cleavage occurs just external to the transmembrane domain and is catalyzed by ADAM-type metalloproteases (8,29). This creates a short-lived intermediate, N TM *, which appears to be recognized through its amino terminus by nicastrin (44), a component of a multiprotein enzyme complex called ␥-secretase. N TM * is then cleaved by ␥-secretase at several sites within the transmembrane domain (10,19,42).…”
mentioning
confidence: 99%